Formation of linear arrays of holes in self-assembled collagen films - Erkan, Melis; Blakney, Kaitlyn; Andrews, Emily; Leslie, Reagan; Ozsan, Eda; Kreplak, Laurent (Frontiers in Soft Matter, 2024)
Collagen is one of the main constituents of mammalian extracellular matrix and is used extensively as a coating for tissue culture dishes and medical implants to promote cell growth and proliferation. By modulating the topography of the collagen coating at the nanometer to micrometer length scales, it is possible to achieve spatial control over cell growth and morphology. In this work, we are exploring the self-assembly of a thin collagen film on a glass substrate as a way to create new nanoscale surface features. By controlling the collagen concentration and adding an oscillatory flow, we are able to enrich the collagen film surface with a localized pattern of ripples oriented perpendicular to the flow direction. We propose that these ripples are the result of dewetting of the collagen film that leads to the formation of adjacent holes. We observe that individual holes form with an anisotropic rim due to the microstructure of the deposited collagen fibril network. This intrinsic anisotropy and the oscillatory flow yield new holes being formed in the film next to existing rims. As holes keep growing deeper, the rims extend along the flow direction, and the holes appear rectangular in shape, which gives the linear array of holes the apparent morphology of a ripple. Overall, we are able to create localized ripples at the surface of collagen films that would be difficult to produce via standard nanofabrication techniques.